Evaluation of physical fitness parameters of hearing impaired adolescents who are active and non-active in sports - A. Uludag; Erkan Calıskan; Ozge Caglar; Tulin Sepetcı (Türk Spor ve Egzersiz Dergisi)
The aim of this study is evaluate the physical fitness parameters of 9 – 17 years old hearing impaired adolescentswho were active and non active in sports. The study was included totally 65 students attended to the Kepezhearing impaired school; 40 (26 male, 14 female) active in sports (participating the team sports at least 3 days aweek) with the mean age of 12.85 ± 2.83 years and 25 (14 male, 11 female) non- active in sports with the mean ageof the 11.48 ± 3.20 years. Physical characteristics, physical fitness and body composition of the subjects have beenevaluated in this study. For statistical analyses; mean values, standard deviations and frequency distributionswere calculated for all variables. Independent samples t- tests was used to compare the active and non-activegroups. As result of statistical analyses stature resting heart rate, flexibility, standing long jump, 20 m sprint,reaction time, hand grip strength, back and leg strength, sit-ups, vertical jump, and percent body fat values werefound significantly different between the active and non-active hearing impaired groups (p lt;0.05). Consequently ithas been revealed that participating the sport would positively influence the physical development, physicalfitness and body composition characteristics of hearing impaired childrens.